1999
DOI: 10.1002/(sici)1521-3757(19990614)111:12<1851::aid-ange1851>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Al22Br20⋅12 THF: das erste polyedrische Aluminiumsubhalogenid – ein Schritt auf dem Weg zu einer neuen Aluminiummodifikation?

Abstract: Das erste polyedrische Aluminiumsubhalogenid Al22Br20⋅12 L entsteht bei der Disproportionierung von AlI‐Bromid‐Lösungen. Der Cluster ist aus einem Al12‐Ikosaeder mit zehn exohedral gebundenen (formal zweiwertigen) Al‐Atomen aufgebaut (siehe Struktur). Ein derartiges homoatomares Gerüst ist bei molekularen Verbindungen unbekannt. Selbst beim Element Bor findet man dieses Gerüst lediglich als Ausschnitt aus der β‐rhomboedrischen Elementmodifikation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
6

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 30 publications
0
7
0
6
Order By: Relevance
“…In contrast, in the case of the only previously obtained Ga 22 cluster with an icosahedral Ga 22 core (without a central Ga atom), [Ga 22 {N(SiMe 3 ) 2 } 10 Br 10 ] 2− ( 3 ),6 the average oxidation number of 0.82 is not very different from that of the GaX starting material. This is also true for the first polyhedral gallium subhalide [Ga 24 X 22 ] ( 4 )7 (average oxidation number 0.92), which can be viewed as a common precursor (possibly in a slightly modified form, such as [Ga 22 X 20 ], which is analogous to the well‐known [Al 22 X 20 ]8) for the numerous Ga 22 clusters (Figure 1). With the P t Bu 2 ligand used here, as in previous cases such as the metalloid clusters [Ga 16 (P t Bu 2 ) 10 ] ( 5 )9 and [Ga 51 (P t Bu 2 ) 14 Br 6 ] 3− ( 6 ),10 we find that the cluster core is linked to the outer shell by additional bonds to bridging P atoms, which facilitates the isolation of unusual Ga n frameworks.…”
Section: Calculated Atomic Volumes In Icosahedral and Body‐centered Cmentioning
confidence: 71%
“…In contrast, in the case of the only previously obtained Ga 22 cluster with an icosahedral Ga 22 core (without a central Ga atom), [Ga 22 {N(SiMe 3 ) 2 } 10 Br 10 ] 2− ( 3 ),6 the average oxidation number of 0.82 is not very different from that of the GaX starting material. This is also true for the first polyhedral gallium subhalide [Ga 24 X 22 ] ( 4 )7 (average oxidation number 0.92), which can be viewed as a common precursor (possibly in a slightly modified form, such as [Ga 22 X 20 ], which is analogous to the well‐known [Al 22 X 20 ]8) for the numerous Ga 22 clusters (Figure 1). With the P t Bu 2 ligand used here, as in previous cases such as the metalloid clusters [Ga 16 (P t Bu 2 ) 10 ] ( 5 )9 and [Ga 51 (P t Bu 2 ) 14 Br 6 ] 3− ( 6 ),10 we find that the cluster core is linked to the outer shell by additional bonds to bridging P atoms, which facilitates the isolation of unusual Ga n frameworks.…”
Section: Calculated Atomic Volumes In Icosahedral and Body‐centered Cmentioning
confidence: 71%
“…GaBr (48 mmol) was cocondensed with toluene (100 mL) and THF (5 mL) according to the literature method 5. A portion (25 ml) of the ca.…”
Section: Methodsmentioning
confidence: 99%
“…Although we have recently synthesized a series of metalloid gallium clusters from GaX‐solution (X=Cl, Br, I),2, 3 no further examples of Gallium subhalides have been reported 4. However, we have shown that the polyhedral aluminum subhalide, [Al 22 X 20 ]⋅12 THF ( 1 ; X=Cl, Br) can be prepared from metastable AlCl or AlBr solution 5. 6 The topology of the 22 aluminium atoms in 1 is unexpected: 10 aluminium atoms are directly bonded by 2c–2e bonds to a central Al 12 icosahedron such that two aluminum atoms at the apexes of the Al 12 icosahedron are “naked”.…”
mentioning
confidence: 99%
“…3) In several earlier publications we discussed to what degree the topology of metalloid clusters can be interpreted as snapshots in the formation of hypothetical modifications of the metals 15. 31, 32 Exemplarily, a supposedly nonmetallic modification of Al with an α‐boron structure shall be mentioned 33. 34 Here we want to study only clusters that contain a core of 12 Ga atoms.…”
mentioning
confidence: 99%